Penerapan Metode Sugestopedia dan Media Lagu Sebagai Upaya Meningkatkan Keterampilan Menulis Cerpen Siswa Kelas XI SMA Negeri 1 Geger Kabupaten Madiun - Ernawati, Sulis; Suharto, V. Teguh; Hadi, Panji Kuncoro (Universitas PGRI Madiun, 2024)
This study aims to (1) describe the improvement of short story writing skills with the application of suggestopedia method and song media in class XI SMA Negeri 1 Geger, (2) describe the improvement of students' activities in class XI SMA Negeri 1 Geger. This type of research is a Classroom Action Research conducted in two cycles, namely cycle I and cycle II. Data collection techniques used test and non-test techniques. Data analysis techniques used qualitative and quantitative. Both techniques were analysed by comparing the test results of cycle I and cycle II. The results showed that in cycle I the average score achieved by students of class XI.3 was 69.3 or included in the sufficient category. While in cycle II the average score achieved was 79.4 and included in the good category. There was an increase from cycle I to cycle II of 10.1 points or 14.6%. Student activity in learning has increased in a positive direction. Students are active in the learning process from the beginning to reflection. Students are more excited, enthusiastic, and earnest when participating in learning to write short stories. Based on the results of the study, it can be concluded that the application of the suggestopedia method and song media can improve the short story writing skills of students of class XI SMAN 1 Geger Madiun Regency.